Changed roles and strategies of professionals in the (co)production of public services - Nicolette van Gestel; Marlot Kuiper; Wiljan Hendrikx (Administrative Sciences, 2019)
This paper investigates the changed roles and strategies of professionals in a context of hybrid welfare state reform. This context exposes public professionals to market regulation and rationalization (new public management), and simultaneously expects them to work across professional borders to co-produce public services together with their clients, colleagues and other stakeholders (new public governance). Adopting a comparative perspective, we studied different types of professionals for their views on the implications of this reform mix on their work. Hence, we investigate "strategy" at the macro level of public sector reform and at the micro level of professionals' responses. The study is based on literature and policy documents, participatory observations and especially (group) interviews with professionals across Dutch hospitals, secondary schools and local agencies for welfare, care or housing. We found that professionals across these sectors, despite their different backgrounds and status, meet highly similar challenges and tensions related to welfare state reform. Moreover, we show that these professionals are not simply passive "victims" of the hybrid context of professionalism, but develop own coping strategies to deal with tensions between different reform principles. The study contributes to understanding new professional roles and coping strategies in welfare state reform, in a context of changing relationships between professions and society.
Keywords: 350; professionals; welfare state reform; new public management; new public governance; professional roles; coping strategies